2020
DOI: 10.1186/s43042-020-00122-z
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the genetic determinant of severity in viral diseases: a case of SARS-Cov-2 infection

Abstract: Background Numerous research studies have identified specific human gene variants that affect enhanced susceptibility to viral infections. More recently is the current pandemic where the SARS-CoV-2 infection has shown a high degree of person-to-person clinical variability. A wide range of disease severity occurs in the patients’ experiences, from asymptomatic cases, mild infections to serious life threatening conditions requiring admission into the intensive care unit (ICU). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…Owing to the fact that the ACE2 gene is located on the X chromosome, it has been suggested that the higher mortality rate among males should possibly be related to its lower expression. Furthermore, estrogen increases the ACE2 expression and activity in women[ 63 , 64 ]. Renin-angiotensin system balance is maintained by the ACE and ACE2 function; thus, ACE2 gene variants or their overexpression lead to renin-angiotensin system imbalance resulting in vasoconstriction, hypercoagulation, fibrosis, alveolar cell apoptosis, increased ROS production, and lung damage overall.…”
Section: Genetic Association Studies and Covid-19 Host Genetics Initiativementioning
confidence: 99%
See 1 more Smart Citation
“…Owing to the fact that the ACE2 gene is located on the X chromosome, it has been suggested that the higher mortality rate among males should possibly be related to its lower expression. Furthermore, estrogen increases the ACE2 expression and activity in women[ 63 , 64 ]. Renin-angiotensin system balance is maintained by the ACE and ACE2 function; thus, ACE2 gene variants or their overexpression lead to renin-angiotensin system imbalance resulting in vasoconstriction, hypercoagulation, fibrosis, alveolar cell apoptosis, increased ROS production, and lung damage overall.…”
Section: Genetic Association Studies and Covid-19 Host Genetics Initiativementioning
confidence: 99%
“…Allele frequency variations of the ACE2 gene in different populations might be due to SNPs. Compared to a global average, the protective variants were found to be of higher frequency in the Asian population, whereas the risk variants were more frequent among the population of European descent[ 10 , 63 ].…”
Section: Genetic Association Studies and Covid-19 Host Genetics Initiativementioning
confidence: 99%
“…The novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), causing the Coronavirus disease 2019 (COVID-19), has affected over 100 million globally with over 2.5 million fatalities to date leading to a global pandemic of unprecedented size (1). COVID-19 symptoms can vary from person to person, leading to a clinical manifestation of disease ranging from asymptomatic to mild infections, through to serious, lifethreatening cases requiring admission to the intensive care unit (ICU) (2,3). The severity of COVID-19 depends on several factors including age, gender, and the presence of existing comorbidities such as diabetes, hypertension, or respiratory disease (4-6); however, it is difficult to predict the future severity of COVID-19 infection at the time of the patients' admission to the hospital.…”
Section: Introductionmentioning
confidence: 99%
“…Conway SPHERE Research Group, Conway Institute, University College Dublin, Dublin, Ireland, 2 School of Biomolecular and Biomedical Science, University College Dublin, Dublin, Ireland, 3 To date, coronavirus disease 2019 (COVID-19) has affected over 100 million people globally. COVID-19 can present with a variety of different symptoms leading to manifestation of disease ranging from mild cases to a life-threatening condition requiring critical care-level support.…”
mentioning
confidence: 99%
“…The COVID-19 is a high contagious disease and spread around the globe within a short time, and the world health organization (WHO) has declared it a pandemic on March 12, 2020 [3] . COVID-19 symptoms can vary from person to person, leading to a clinical manifestation of disease ranging from asymptomatic to mild infections, through to serious, life threatening cases requiring admission to the intensive care unit (ICU) [4,5] . The severity of COVID-19 depends on several factors including age, gender, and the presence of existing comorbidities such as diabetes, hypertension, or respiratory disease [6][7][8] ; however, it is difficult to predict the future severity of COVID-19 infection at the time of the patients' admission to the hospital.…”
Section: Introductionmentioning
confidence: 99%